Penyuluhan Pemanfaatan Teknologi Informasi Sebagai Peningkatan SDM Kesejahteraan Sosial - Subandi Subandi; Wiharto, Yudi; Mufti, Mufti; Gata, Grace; Diana, Anita (Jurnal Kabar Masyarakat, 2024)
This community service aims to improve the competence of Human Resources (HR) in the field of social welfare through counseling on the use of information technology. In the digital era, information technology has an important role in improving the effectiveness and efficiency of social services, but there are still many social welfare actors who have not optimally used it. This activity is carried out through counseling which includes the introduction of various digital applications and platforms that can be used to facilitate social work, such as data management, communication, and information dissemination. The counseling method is carried out through presentations, interactive discussions, and simulations of the use of relevant technology. The ultimate goal of this program is to improve HR skills in utilizing information technology appropriately, so that it can support the improvement of the quality of social services that are faster, more accurate, and more equitable. Thus, this program is expected to be able to provide a positive impact in improving the quality of technology-based social welfare services.